Perspectives and commitments of smart education in Russia - A. V. Bodyako; T. M. Rogulenko; S. V. Ponomareva; M. V. Krayushkina (Вестник университета)
The challenges of modern world are not only numerous, but also diverse – from a positive impact on the development of society to clearly unfriendly attacks in the economy, politics, science and education. Positive trends are associated with the smart education development, a new cognitive sphere that involves complex communication of all participants in the educational process in order to continuously improve the methods and technologies of the knowledge economy. In the digital paradigm of social development management, the knowledge sources are not only various formats (digital and paper) of textbooks, manuals and other, but also a close creative union between a teacher and a student, which allows not to get lost in the endless expanses of the Internet. The article highlights the trends in the domestic and foreign authors’ studying problems and prospects for the development of smart education. A mechanism for transforming the established methods of vocational training in Russian universities into a new concept of smart education is proposed. The principles of digital education format are formulated. The article content is determined by the methodology for the knowledge economy development: the basic principles of smart education and conceptually important methods for educational process organising. The studies of professors A.A. Bubenchikov, V.V. Glukhov, M.K. Novikov, V.P. Tikhomirov, etc., facilitated the idea of a prospective smart university concept development. The article is based on scientific research methods such as: comparison, analysis and synthesis, induction and deduction, historical and logical methods, positive and normative analysis, and the method of scientific logic.